Early appendectomy for appendicular mass: operative findings and outcome in 220 children-a developing country perspective - M. A. Mushfiqur Rahman; Tanvir Kabir Chowdhury; Mohammad Zonaid Chowdhury; Md. Abdullah Al Farooq (SpringerOpen, 2020)
Abstract Background Lump or mass formation due to delayed presentation after appendicitis is common, and it is frequently complicated by perforation, gangrene, pus, or abscess formation. Care of patients and management vary between developed world and developing country. The aim of the study is to analyze outcome of early surgery for appendicular mass from a developing country perspective. 220 patients of appendicular mass who underwent early appendectomy over a period of 5 years in the Department of Pediatric Surgery, at author's institute were retrospectively reviewed. Early appendectomy was defined as appendectomy done within 24 h of admission. Presentation, examination findings, investigations, type of surgery, operative findings, post-operative complications, and hospital stay were analyzed. Results Age of patients ranged from 2 to 12 years (mean 9.04 ± 2.54 years) and male to female ratio was 2:1. Abdominal pain was the most common presentation followed by vomiting and fever. Mean pain duration was 4.35 ± 4.23 days. There was raised temperature in 140 (63.64%) patients, 154 (74.04%) had tachycardia, and 75.86% had raised WBC count. Laparoscopic appendectomy was done in 31 (14.09%) patients, and the rest 189 (85.91%) patients underwent open surgery. Perforated appendix was the most common (171 patients, 77.73%) peri-operative finding followed by formation of pus (135 patients, 61%). Pus was found more in patients less than 5 years old (18 patients out of 23) than patients more than 5 years old (114 patients out of 197) (P = 0.045). Younger patients also had significantly more complications (39.13% vs 17.26%, P = .000) and hospital stays (mean 15.61 days vs 9.87 days, P = 0.014) than older boys. Complications developed in 42 (19.09%) patients, and wound dehiscence (26 patients, 11.82%) was the most common complication. Conclusion Early appendectomy for appendicular mass is a feasible option in the developing world, and laparoscopic appendectomy has good prospect.